2012
DOI: 10.1007/s00066-012-0162-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after neoadjuvant radiochemotherapy in locally advanced noninflammatory breast cancer and predictive factors for a pathologic complete remission

Abstract: pCR identifies patients with a significantly better prognosis for long-term survival. However, a long time interval to surgery (> 2 months) increases the probability of pCR after NRT-CHX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…A number of older case series and single arm trials report on preoperative RT with or without concomitant chemotherapy [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (Table 1). In those that report on receptor status, hormone receptor positive tumours were less likely to achieve pathological complete response to chemoradiation (chemoRT) than other subtypes [16,17], which is unsurprising given the better complete pathological response rates following chemotherapy for higher risk subgroups.…”
Section: -Downstaging Of the Tumour To Enable Conservative Surgerymentioning
confidence: 99%
“…A number of older case series and single arm trials report on preoperative RT with or without concomitant chemotherapy [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (Table 1). In those that report on receptor status, hormone receptor positive tumours were less likely to achieve pathological complete response to chemoradiation (chemoRT) than other subtypes [16,17], which is unsurprising given the better complete pathological response rates following chemotherapy for higher risk subgroups.…”
Section: -Downstaging Of the Tumour To Enable Conservative Surgerymentioning
confidence: 99%
“…With the progress of examination techniques, early-stage cancer can now be detected and treated with the development of multidisciplinary therapies. Surgery and radiotherapy are used for local control, whereas chemotherapy is used for systemic control (28). The most recent examination techniques occasionally enable the detection of early-stage cancer, oligometastases and oligo-recurrence (9–11).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of LABC have reported good pathological response rates with preoperative chemoradiotherapy, but all used “conventional” radiation techniques, often via tangential fields. Matuschek et al [11] reported a series of 315 LABC patients (cT1-cT4/cN0-N1). Preoperative EBRT delivered 50 Gy (5 × 2 Gy/week) to the whole breast, SCV/ICF nodes (255 of 315 patients), and IMC with a boost in 214 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have used preoperative radiotherapy (combined with chemotherapy) in an attempt to downsize the tumor [611] making it amenable to surgery. However, these studies have only used conventional radiation techniques with considerable limitations in target volume coverage and sparing normal tissues.…”
Section: Introductionmentioning
confidence: 99%